Unsteady Magnetohydrodynamic Flow in the Presence of Permeable Medium through an Upstanding Channel with Persistent Suction and Heat Source - Mehta, Tripti; Mehta, Ruchika; Kumar, Devendra (Science & Technology Asia, 2020)
The present study explores unsteady magnetohydrodynamic, incompressible viscous fluid flow through upstanding equidistant plates in the presence of permeable media, persistent heat flux and heat source. The flow is constrained due to the flow between two equidistant plates, one of which is moving and other is at rest, and the occurrence of free convection because of the stationary wall with persistent temperature while heat flux is persistent on the wall with a uniform upstanding motion in its self plane. The fluid is considered emitting/absorbing but medium is non-scattering, so taking it as grey and to describe the radiative heat flux with persistent suction we used the Rosseland approximation. Numerical results for the velocity and temperature distribution for various physical parameters as well as the local skin friction coefficient and local Nusselt number are discussed numerically and shown through graphs.